International Standard Bibliographic Description (ISBD) as standard for quality book publishing in Nigeria - Enang, Uduak U. (2011)
This study examines international standard bibliographic description (ISBD) as standard for quality book publishing in Nigeria. It discusses ISBD as it affects quality book publishing. Three Universities in the South-South region and 250 publishers sampled from six states of the federation were used for the study. The instruments used were validated questionnaire and standardized checklist of the book. One null hypothesis was formulated and tested. The data collected were analyzed using simple percentages and Pearson Product Moment Correlation Coefficient (PPMC). The finding of the study shows that there is a significant relationship between ISBD and the quality of books published in Nigeria with regard to authorship, title, place of publication, year of publication, publisher’s name, ISBN, copyright, bibliography and index. The study concluded that ISBD adds quality to published books.